Legal Aspects of Transforming Videos into Non-Fungible Tokens (NFT) Based on Copyright Law No. 28 of 2014 - Febrian, Kelvin Febrian Siga Sari; Kadek Julia Mahadewi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The main objective of this paper is to analyze in depth the video transformed into non-fungible token (NFT) in the context of copyright protection as regulated in Copyright Law No. 28 of 2014. The focus of the discussion is directed at how the process of transforming a video into NFT can be qualified as a form of format change that is recognized as a new creation based on applicable legal provisions, especially Article 40 paragraph (1) letter n of the Copyright Law. This study uses a normative legal research method, which is based on an analysis of applicable written legal norms. The approach used is a conceptual and legislative approach, by examining the provisions in relevant laws and regulations, especially the Law. The results of this study indicate that a video transformed into an NFT is a form of legally valid transformed work and automatically obtains copyright protection. This protection is important to ensure that video creators retain exclusive rights to their work, even though it has undergone a format change. To strengthen legal protection, creators can register their NFT video works, so that their legal status becomes clearer. In the event of use of a work by another party without permission, especially for commercial purposes, the creator or copyright holder has the right to take legal steps, including reporting the violation to the relevant authorities for appropriate law enforcement processes.